Discourse Markers in Conversational Storytelling and Its Treatment in the Indonesian version of Selected Articles in Koreana Magazine - Kurniati, Nur Utami Sari’at (Universitas Pakuan, 2023)
The paper presents an analysis of discourse markers used in a conversational storytelling in the Interview section in Koreana quarterly magazine. There are nine discourse markers found in the English editions of 2020, with and has the highest occurrence, and well and you know have the lowest. The markers appear either on their own or co-occur with other marker in a cluster. Those discourse markers are either fully or partially translated into their Indonesian equivalences or omitted due to various reasons.Keywords: discourse markers, conversational storytelling, Indonesian translation